Dataset from The Third Plague Pandemic in Europe. - Barbara Bramanti; Katharine R. Dean; Lars Walløe; Nils Chr. Stenseth (2019)
Collected data for plague cases in Europe from the Public Health Reports (formerly Bulletins of the Public Health and Weekly Abstract of Sanitary Reports) between 1879-1950.